Circulating Endometrial Cells in Women With Spontaneous Pneumothorax - Kiss, Imrich; Pospisilova, Eliska; Kolostova, Katarina; Maly, Vilem; Stanek, Ivan; Lischke, Robert; Schutzner, Jan; Pawlak, Ireneusz; Bobek, Vladimir (Chest, 2020)
BACKGROUND: The occurrence of catamenial pneumothorax (CP) is rare, and the awareness of this diagnosis among physicians is insufficient. CP is highly correlated with pelvic endometriosis and remains the most common form of thoracic endometriosis syndrome. Circulating endometrial cells (CECs) have been previously detected in patients with pelvic endometriosis. Could CECs bring new insights into pneumothorax management? METHODS: This study aims to describe the occurrence and molecular characteristics of CECs in women with spontaneous pneumothorax (SP) (N = 20) with high suspicion of its catamenial character. CECs were enriched from peripheral blood by size-based separation (MetaCell). In addition to cytomorphology, gene expression profiling of captured cells was performed for 24 endometriosis-associated genes. RESULTS: CECs were present in all 20 patients with SP. Enriched CECs exhibited four character features: epithelial, stem cell-like, stroma-like, and glandular. However, not all of them were present in every sampling. Gene expression profiling revealed two distinct phenotypes of CECs in SP and/or CP: one of them refers to the diaphragm openings syndrome and the other to endometrial tissue pleural implantations. Comparisons of the gene expression profiles of CECs in pneumothorax (CECs-SP group) with CECs in pelvic endometriosis (CECs-non-SP group) have revealed significantly higher expression of HER2 in the CECs-SP group compared with the CECs-non-SP group. CONCLUSIONS: This proof-of-concept study demonstrates successful isolation and characterization of CECs in patients with SP. Identification of CECs in SP could alert endometriosis involvement and help early referral to gynecologic consultation for further examination and treatment.
Keywords: dospělí; endometrióza; CA-125 Antigen; Female; keratin-18; circulating endometrial cells; MetaCell; Pneumothorax; Adult; mladý dospělý; ženské pohlaví; endometrium; Endometriosis; lidé; vimentin; Liquid Biopsy; Keratin-18; Vimentin; membránové proteiny; studie případů a kontrol; Pleural Diseases; in vitro; Receptor, ErbB-2; gene expression profiling; receptor erbB-2; endometriosis; biomarker; mucin 1; catamenial pneumothorax; Case-Control Studies; antigen CA-125; nemoci pleury; Young Adult; Mucin-1; liquid biopsy; Endometrium; Membrane Proteins; lidé středního věku; pneumotorax; transkriptom; culturing; Transcriptome; tekutá biopsie; Middle Aged; Humans